2022
DOI: 10.3390/ijerph192013714
|View full text |Cite
|
Sign up to set email alerts
|

Patient Acceptability of Home Monitoring for Neovascular Age-Related Macular Degeneration Reactivation: A Qualitative Study

Abstract: Neovascular age-related macular degeneration (nAMD) is a chronic, progressive condition and the commonest cause of visual disability in older adults. This study formed part of a diagnostic test accuracy study to quantify the ability of three index home monitoring (HM) tests (one paper-based and two digital tests) to identify reactivation in nAMD. The aim of this qualitative research was to investigate patients’ or participants’ views about acceptability and explore adherence to weekly HM. Semi-structured inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Importantly, this should be alongside human physicians, instead of replacing them, and artificial intelligence outputs should be transparent and verifiable wherever possible. Prospective randomized trials, real-world studies, and economic evaluations are highly important to demonstrate the value of artificial intelligence-based home monitoring, and should include patient-reported outcome measures and qualitative studies to evaluate patients’ experiences and attitudes [52 ▪ ]. These have been conducted for some approaches and indications and are ongoing or planned for others.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this should be alongside human physicians, instead of replacing them, and artificial intelligence outputs should be transparent and verifiable wherever possible. Prospective randomized trials, real-world studies, and economic evaluations are highly important to demonstrate the value of artificial intelligence-based home monitoring, and should include patient-reported outcome measures and qualitative studies to evaluate patients’ experiences and attitudes [52 ▪ ]. These have been conducted for some approaches and indications and are ongoing or planned for others.…”
Section: Discussionmentioning
confidence: 99%
“…Despite studies reporting positive usability data and favourable responses from patients, researchers have noted the possible difficulties of introducing some patients to digital technologies. It should be noted that studies reporting usability or patient satisfaction data are in the minority, and only one reports rich qualitative data on patient experience [ 70 ]. Data from the MONARCH study, obtained from semi-structured interviews, has shown home monitoring methods to be acceptable to patients with nAMD and their caregivers [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that studies reporting usability or patient satisfaction data are in the minority, and only one reports rich qualitative data on patient experience [ 70 ]. Data from the MONARCH study, obtained from semi-structured interviews, has shown home monitoring methods to be acceptable to patients with nAMD and their caregivers [ 70 ]. Obtaining further data of this kind will allow greater understanding of how remote monitoring technologies can be developed and implemented to best meet patient need and maximise engagement.…”
Section: Discussionmentioning
confidence: 99%
“…The Monitoring for Neovascular Age-Related Macular Degeneration Reactivation at Home (MONARCH) study was a multicenter, diagnostic accuracy cohort study to estimate the performance of 3 home-monitoring vision tests in detecting nAMD activation in patients undergoing treatment for active nAMD. Additional details can be found in the published protocol and an article using qualitative methodology to capture patient acceptability during the study . Ethical approval was granted by the Northern Ireland Health and Social Care Research Ethics Committee A (Reference number: 17/NI/0235) on January 29, 2018, and our study design and execution adhered to the Declaration of Helsinki.…”
Section: Methodsmentioning
confidence: 99%